Analisis Penggunaan Media Puppet Show untuk Peningkatan Kemampuan Menyimak dan Bercerita Siswa - Zulfikar Nurhanani; Bambang Budi Wiyono; Nurchasanah Nurchasanah (Graduate School of Universitas Negeri Malang, 2020)
Abstract: Supporting students can develop well supporting the selection of appropriate media specifically in developing listening and storytelling abilities. Researchers looking for the influence of the shadow play media show the ability to listen and tell stories in grade II elementary school. This study uses quantitative research with the design of Quasi-Experiment Pretest and posttest Control Group Design. Displaying performance shows using the Puppet Show media has been in accordance with the steps of the activities that are developed, and there is a development with the use of the Puppet Performance media to the ability to listen and tell the second grade students with sig. the experimental class of 0.144 which is smaller than 0.05 in the control class.Abstrak: Kemampuan berbahasa siswa dapat berkembang dengan baik apabila didukung pemilihan media yang tepat khususnya dalam pengembangan kemampuan menyimak dan bercerita. Peneliti mencari pengaruh media puppet show terhadap kemampuan menyimak dan bercerita kelas II SD. Penelitian ini menggunakan pendekatan penelitian kuantitatif dengan rancangan Quasi-Experiment Pretest and postest Control Group Design. Hasilnya menunjukkan pelaksanaan pembelajaran dengan menggunakan media Puppet Show telah sesuai dengan langkah kegiatan yang dikembangkan, dan ada pengaruh dengan penggunaan media Puppet Show terhadap kemampuan menyimak dan bercerita siswa kelas II dengan nilai sig. kelas eksperimen yaitu 0,144 yang lebih kecil dari 0,05 pada kelas kontrol.